Reflective synergistic film and synergistic photovoltaic module with same
By laying a reflective enhancement film made of mesoporous composite materials and nanomaterials in the gap position of the photovoltaic module cell, the problems of light loss and cell damage in the prior art are solved, and higher power output and bonding of photovoltaic modules are achieved. The battery is damaged and fragmented.
Patent Information
- Application Number
- CN202411247458.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
In existing photovoltaic modules, when the reflective material is constructed on the backglass or backplane, light loss will occur due to the existence of the packaging film, and the construction location is prone to the battery cracks or fragments, which will not maximize the use of light.
Using a reflective enhancement film including a buffer layer and a substrate layer, a reflective enhancement film for the gap between photovoltaic module cells is prepared by combining mesoporous composite materials with nanomaterials, thereby increasing the reflectivity of the 330-380nm ultraviolet region. and secured by positioning tape to avoid battery damage.
It significantly improves the output power of photovoltaic modules, enhances the adhesion between the buffer layer and the battery, and the adhesion between the substrate layer and the adhesive film, avoids battery cracks and fragments, and increases the power more than when constructed on glass. Significant.
Smart Images

Figure BDA0005031221650000081 
Figure BDA0005031221650000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic modules, and in particular relates to a reflective efficiency-enhancing film and an efficiency-enhancing photovoltaic module having the same. Background Art
[0002] Photovoltaic grid parity, cost reduction and efficiency improvement have always been important topics for joint research in the industry. The gap between the cells of a photovoltaic module accounts for about 3-7% of the entire module. Usually, this part of the light can be utilized by various methods such as glazing, coating, and reflective materials, so that this part of the light is fully reflected at the glass and air interface of the photovoltaic module, and then returns to the cell again, thereby increasing the output power of the photovoltaic module. Regardless of the method, the current reflective materials are limited to construction on the back glass or backboard. However, due to the presence of a certain thickness of encapsulation film between the back glass or backboard and the battery, the construction of reflective materials on the back glass or backboard will cause loss of the reflected light, and the light cannot be maximized. In addition, changing the laying position of the reflective material is very likely to cause hidden cracks or fragments in the battery. Summary of the invention
[0003] In order to solve the technical problems existing in the prior art, the object of the present invention is to provide a reflective efficiency-enhancing film and an efficiency-enhancing photovoltaic module having the same.
[0004] In order to achieve the above purpose and the above technical effect, the technical solution adopted by the present invention is:
[0005] A reflective synergistic film comprises a buffer layer and a substrate layer. The buffer layer is prepared from raw materials comprising ethylene polymers, mesoporous composite materials, fillers and additives. The substrate layer is prepared from raw materials comprising propylene polymer alloys, mesoporous composite materials, fillers and additives.
[0006] Furthermore, the buffer layer comprises the following components by weight:
[0007] Ethylene polymer 55-93 parts
[0008] Mesoporous composite material 2-12 parts
[0009] Filler 5-30 parts
[0010] Additives 0.1-3 parts.
[0011] Furthermore, the substrate layer comprises the following components by weight:
[0012] Propylene polymer alloy 57-90 parts
[0013] Mesoporous composite material 5-25 parts
[0014] Filler 5-25 parts
[0015] Additives 0.1-3 parts.
[0016] Furthermore, the mesoporous composite material is composited by a mesoporous material and a nanomaterial, the mesoporous material is selected from at least one of MCM-41, SBA-15, and MCM-48, the nanomaterial is selected from at least one of nano zinc oxide, nano calcium carbonate, and nano barium sulfate, and the particle size of the nanomaterial is 10-200nm.
[0017] Furthermore, the thickness of the buffer layer is 30-100 μm, the thickness of the substrate layer is 20-100 μm; and the propylene polymer alloy is an alloy of a propylene polymer and an ethylene polymer.
[0018] Furthermore, the ethylene polymer has a melting point of 70-120°C and a hardness of <80A, and is selected from one or more combinations of polyethylene, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer, maleic anhydride grafted ethylene-butene copolymer, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene-hexene copolymer.
[0019] Furthermore, the propylene polymer is selected from one or more combinations of homopolypropylene, copolymer polypropylene and block polypropylene.
[0020] Furthermore, the filler is selected from a combination of one or more of titanium dioxide, calcium carbonate, talc, mica, barium sulfate, silicon dioxide, and glass microspheres.
[0021] Furthermore, the additives include an antioxidant and a light stabilizer, the antioxidant is a primary antioxidant or a mixture of a primary antioxidant and a secondary antioxidant, and the light stabilizer is an ultraviolet absorber and / or an ultraviolet stabilizer.
[0022] The present invention also discloses a photovoltaic module, comprising the reflective film as described above, wherein the reflective film is laid in the gap between the photovoltaic module cells and the lower packaging film.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention discloses a reflective synergistic film and a photovoltaic module having the same. The mesoporous composite material is prepared by compounding a mesoporous material with a nanomaterial and then used for preparing a buffer layer and a substrate layer, which is beneficial to improving the reflectivity in the ultraviolet region of 330-380nm, the adhesion between the buffer layer and the battery, and the adhesion between the substrate layer and the adhesive film. The reflective synergistic film is applied to the gap between the cells on the photovoltaic cell to avoid hidden cracks and fragments of the cell. Compared with the application on glass, the module power can be greatly improved. DETAILED DESCRIPTION
[0025] The present invention is described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0026] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or critical elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.
[0027] The invention discloses a reflective synergistic film, comprising a buffer layer and a substrate layer, wherein the thickness of the buffer layer is 30-100 μm, the thickness of the substrate layer is 20-100 μm, and the reflective synergistic film is constructed at the gap position of the battery cells on the photovoltaic cell and fixed by a positioning tape.
[0028] The raw materials for preparing the buffer layer include ethylene polymers, mesoporous composite materials, fillers and additives. In parts by weight, the buffer layer includes the following components:
[0029] Ethylene polymer 55-93 parts
[0030] Mesoporous composite material 2-12 parts
[0031] Filler 5-30 parts
[0032] Additives 0.1-3 parts.
[0033] The raw materials for preparing the substrate layer include propylene polymer alloy, mesoporous composite material, filler and additive. In parts by weight, the substrate layer includes the following components:
[0034] Propylene polymer alloy 57-90 parts
[0035] Mesoporous composite material 5-25 parts
[0036] Filler 5-25 parts
[0037] Additives 0.1-3 parts.
[0038] The mesoporous composite material is composited by mesoporous material and nanomaterial, the mesoporous material is selected from at least one of MCM-41, SBA-15 and MCM-48, the nanomaterial is selected from at least one of nano zinc oxide, nano calcium carbonate and nano barium sulfate, and the particle size of the nanomaterial is 10-200nm.
[0039] The propylene polymer alloy is an alloy of a propylene polymer and an ethylene polymer, and the addition ratio of the propylene polymer in the propylene polymer alloy is greater than 55%.
[0040] The ethylene polymer has a melting point of 70-120°C and a hardness of <80A, and is selected from one or more combinations of polyethylene, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer, maleic anhydride grafted ethylene-butene copolymer, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene-hexene copolymer.
[0041] The propylene polymer is selected from one or more combinations of homopolypropylene, copolymer polypropylene and block polypropylene.
[0042] The filler is selected from one or more combinations of titanium dioxide, calcium carbonate, talc, mica, barium sulfate, silicon dioxide, and glass microspheres.
[0043] The additives include antioxidants and light stabilizers. The antioxidant is a primary antioxidant or a mixture of a primary antioxidant and a secondary antioxidant. The light stabilizer is an ultraviolet absorber and / or an ultraviolet stabilizer.
[0044] The main antioxidant is a hindered phenol antioxidant (such as antioxidant 1010, etc.) or a hindered phenol phosphite synergistic antioxidant.
[0045] The secondary antioxidant is a phosphite or thioester antioxidant.
[0046] The ultraviolet absorber is selected from one or more combinations of benzophenone, benzotriazole or triazine ultraviolet absorbers.
[0047] The UV stabilizer is a hindered amine UV stabilizer, such as light stabilizer 2020.
[0048] The invention also discloses a photovoltaic module, which comprises a front glass plate, a front encapsulation film, a battery, a reflective enhancement film, a rear encapsulation film, and a back glass or a back plate, which are arranged in sequence from front to back.
[0049] The present invention also discloses a method for preparing a photovoltaic module, comprising the following steps:
[0050] Lay the front glass → lay the front packaging film → lay the battery → lay the reflective enhancement film in the gap between the battery cells (lay it vertically and horizontally respectively) → stick the positioning tape → lay the rear packaging film → lay the back glass or back panel; enter the laminating machine for lamination.
[0051] Example 1
[0052] A reflective synergistic film comprises a buffer layer and a substrate layer. The reflective synergistic film is applied to the gap between cells on a photovoltaic cell and fixed by a positioning tape.
[0053] The buffer layer comprises the following components by weight:
[0054] Ethylene-butene copolymer 62.4 parts
[0055] Mesoporous composite material 12 parts
[0056] 25 parts of titanium dioxide
[0057] Antioxidant 1010 0.1 parts
[0058] Light stabilizer 2020 0.5 parts.
[0059] The melting point of ethylene-butene copolymer is 85°C and the Shore hardness is 52A.
[0060] The substrate layer comprises the following components by weight:
[0061] Copolymer polypropylene 38 parts
[0062] Polyethylene 26.4 parts
[0063] Mesoporous composite material 10 parts
[0064] 25 parts of titanium dioxide
[0065] Antioxidant 1010 0.1 parts
[0066] Light stabilizer 2020 0.5 parts.
[0067] The mesoporous composite material is a composite material of SBA-15 and nano-barium sulfate.
[0068] A method for preparing a reflective enhancement film comprises the following steps:
[0069] 1) Weigh 62.4 parts of ethylene-butene copolymer, 12 parts of mesoporous composite material, 25 parts of titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020, add them into an extruder and mix them evenly, then extrude and granulate them at 220° C., and dry them to obtain a buffer layer masterbatch;
[0070] Weigh 38 parts of copolymerized polypropylene, 26.4 parts of polyethylene, 10 parts of mesoporous composite material, 25 parts of titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020, add them into an extruder and mix them evenly, then extrude and granulate them at 220° C., and dry them to obtain a masterbatch of the substrate layer;
[0071] 2) The buffer layer masterbatch and the substrate layer masterbatch are extruded through a multi-layer casting machine to obtain the desired reflective enhancement film, wherein the thickness of the buffer layer is 50 μm and the thickness of the substrate layer is 50 μm.
[0072] A method for preparing a photovoltaic module with enhanced efficiency comprises the following steps:
[0073] Lay the front glass → lay the front packaging film → lay the battery → lay the reflective enhancement film in the gap between the battery cells (the buffer layer faces the battery side, laid longitudinally and transversely respectively) → stick the positioning tape → lay the rear packaging film → lay the back glass or back panel; enter the laminator for lamination.
[0074] Example 2
[0075] The buffer layer comprises the following components by weight:
[0076] Ethylene-octene copolymer 67.4 parts
[0077] Mesoporous composite material 7 parts
[0078] 25 parts of titanium dioxide
[0079] Antioxidant 1010 0.1 parts
[0080] Light stabilizer 2020 0.5 parts.
[0081] The melting point of ethylene-octene copolymer is 82°C and the Shore hardness is 66A.
[0082] The substrate layer comprises the following components by weight:
[0083] Copolymer polypropylene 40 parts
[0084] Polyethylene 27.4 parts
[0085] Mesoporous composite material 7 parts
[0086] 25 parts of titanium dioxide
[0087] Antioxidant 1010 0.1 parts
[0088] Light stabilizer 2020 0.5 parts.
[0089] The mesoporous composite material is a composite material of MCM-41 and nano zinc oxide.
[0090] The rest is the same as in Example 1.
[0091] Example 3
[0092] The buffer layer comprises the following components by weight:
[0093] Ethylene-butene copolymer 69.4 parts
[0094] Mesoporous composite material 5 parts
[0095] 25 parts of titanium dioxide
[0096] Antioxidant 1010 0.1 parts
[0097] Light stabilizer 2020 0.5 parts.
[0098] The melting point of ethylene-butene copolymer is 85°C and the Shore hardness is 52A. The substrate layer comprises the following components by weight:
[0099] Copolymer polypropylene 40 parts
[0100] Polyethylene 29.4 parts
[0101] Mesoporous composite material 5 parts
[0102] 25 parts of titanium dioxide
[0103] Antioxidant 1010 0.1 parts
[0104] Light stabilizer 2020 0.5 parts.
[0105] The mesoporous composite material is a composite material of MCM-48 and nano-calcium carbonate. The rest is the same as in Example 1.
[0106] Comparative Example 1
[0107] The buffer layer comprises the following components by weight:
[0108] Ethylene-butene copolymer 62.4 parts
[0109] SBA-15 12 parts
[0110] 25 parts of titanium dioxide
[0111] Antioxidant 1010 0.1 parts
[0112] Light stabilizer 2020 0.5 parts.
[0113] The melting point of ethylene-butene copolymer is 85°C and the Shore hardness is 52A. The substrate layer comprises the following components by weight:
[0114] Copolymer polypropylene 38 parts
[0115] Polyethylene 26.4 parts
[0116] SBA-15 10 parts
[0117] 25 parts of titanium dioxide
[0118] Antioxidant 1010 0.1 parts
[0119] Light stabilizer 2020 0.5 parts.
[0120] The rest is the same as in Example 1.
[0121] Comparative Example 2
[0122] The buffer layer comprises the following components by weight:
[0123] Ethylene-butene copolymer 62.4 parts
[0124] 12 parts of nano barium sulfate
[0125] 25 parts of titanium dioxide
[0126] Antioxidant 1010 0.1 parts
[0127] Light stabilizer 2020 0.5 parts.
[0128] The melting point of ethylene-butene copolymer is 85°C and the Shore hardness is 52A. The substrate layer comprises the following components by weight:
[0129] Copolymer polypropylene 38 parts
[0130] Polyethylene 26.4 parts
[0131] 10 parts of nano barium sulfate
[0132] 25 parts of titanium dioxide
[0133] Antioxidant 1010 0.1 parts
[0134] Light stabilizer 2020 0.5 parts.
[0135] The rest is the same as in Example 1.
[0136] Comparative Example 3
[0137] The buffer layer comprises the following components by weight:
[0138] Ethylene-butene copolymer 62.4 parts
[0139] 37 parts of titanium dioxide
[0140] Antioxidant 1010 0.1 parts
[0141] Light stabilizer 2020 0.5 parts.
[0142] The melting point of ethylene-butene copolymer is 85°C and the Shore hardness is 52A. The substrate layer comprises the following components by weight:
[0143] Copolymer polypropylene 38 parts
[0144] Polyethylene 26.4 parts
[0145] 35 parts of titanium dioxide
[0146] Antioxidant 1010 0.1 parts
[0147] Light stabilizer 2020 0.5 parts.
[0148] The rest is the same as in Example 1.
[0149] Comparative Example 4
[0150] The difference between this comparative example and Example 1 is that in this comparative example, only a substrate layer is fixed at the gap between the solar cells on the photovoltaic cell by a positioning tape, the thickness of the substrate layer is 100 μm, and there is no buffer layer.
[0151] The rest is the same as in Example 1.
[0152] Comparative Example 5
[0153] The difference between this comparative example and Example 1 is that in this comparative example, the reflective efficiency enhancement film is fixed on the back glass of the photovoltaic cell. The specific steps are as follows:
[0154] Lay the front glass → lay the front packaging film → lay the battery → lay the rear packaging film → lay the back glass containing the reflective enhancement film; enter the laminating machine for lamination.
[0155] The rest is the same as in Example 1.
[0156] The following tests were performed on Examples 1-3 and Comparative Examples 1-5:
[0157] Reflectivity refers to IEC62788-2-1 test, test band 330-1100nm (distinguishing between 330-380nm and 380-1100nm tests);
[0158] The test method for the adhesion between the buffer layer and the battery is as follows: the sample is cut into strips with a width of 1 cm, and placed in a laminator in the order of glass / encapsulation film / battery / synergistic film from bottom to top for lamination. The lamination temperature is 120°C for the first chamber and 140°C for the second chamber. The lamination time is 18 minutes. After lamination, the peel strength between the sample and the battery is tested using a tensile test machine.
[0159] The adhesion test method between the substrate layer and the film is as follows: cut the sample into small strips with a width of 1 cm, stack them in the order of reflective enhancement film (substrate layer with film surface attached) / release paper / film / glass, put them into a laminator for lamination, the lamination temperature is 120°C for one chamber and 140°C for the second chamber, the lamination time is 18 minutes, and after lamination, a tensile tester is used to test the peel strength between the substrate layer and the film.
[0160] The test results are shown in Table 1.
[0161] Table 1
[0162]
[0163]
[0164] From the data in Table 1, we can see that:
[0165] The reflectivity of Examples 1-3 in the ultraviolet region of 330-380 nm is all >50%, the adhesion between the buffer layer and the battery is all >32 N / cm, the adhesion between the substrate layer and the adhesive film is all >33 N / cm, the module power is all >577 W, and the appearance is OK;
[0166] Comparing Example 1 with Comparative Examples 1-2, Comparative Example 1 does not contain nanomaterials, and Comparative Example 2 does not contain mesoporous materials. The reflectivity of Example 1 in the ultraviolet region of 330-380nm is greater than the reflectivity of Comparative Example 1 in the ultraviolet region of 330-380nm (30.65%) and the reflectivity of Comparative Example 2 in the ultraviolet region of 330-380nm (15.42%), indicating that only by combining mesoporous materials and nanomaterials can the reflectivity of the ultraviolet region of 330-380nm be improved, and only using mesoporous materials or nanomaterials cannot improve the reflectivity of the ultraviolet region of 330-380nm;
[0167] Comparing Example 1 with Comparative Examples 1-2, Comparative Example 1 does not contain nanomaterials, and Comparative Example 2 does not contain mesoporous materials. The adhesion between the buffer layer and the battery and the adhesion between the substrate layer and the adhesive film in Example 1 are both greater than those in Comparative Examples 1-2, indicating that only by combining mesoporous materials and nanomaterials can the adhesion between the buffer layer and the battery and the adhesion between the substrate layer and the adhesive film be improved, and only using mesoporous materials or nanomaterials cannot improve the adhesion between the buffer layer and the battery and the adhesion between the substrate layer and the adhesive film;
[0168] Comparing Example 1 with Comparative Examples 1-2, Comparative Example 1 does not contain nanomaterials, and Comparative Example 2 does not contain mesoporous materials. The module power of Example 1 is greater than that of Comparative Examples 1-2, indicating that only by combining mesoporous materials and nanomaterials can the reflectivity in the ultraviolet region be improved, thereby improving the module power generation. Using only mesoporous materials or nanomaterials cannot improve the module power generation.
[0169] Comparing Example 1 with Comparative Example 3, since Comparative Example 3 does not contain a mesoporous composite material, there is basically no reflectivity in the ultraviolet region of 330-380nm, indicating that only by combining the mesoporous material and the nanomaterial can the reflectivity in the ultraviolet region of 330-380nm be improved;
[0170] The reflectivity of Example 1 and Comparative Examples 1-3 in the visible and near-infrared region of 380-1100 nm is substantially the same, indicating that the addition of the mesoporous composite material will not affect the reflectivity in this band of 380-1100 nm;
[0171] Compared with Example 1 and Comparative Example 4, since Comparative Example 4 does not have a buffer layer, cracks occur, and the battery power also decreases significantly compared with Example 1, indicating that only by compounding the buffer layer and the substrate layer can the desired reflective efficiency-enhancing film and efficiency-enhancing photovoltaic module be produced;
[0172] Comparing Example 1 with Comparative Example 5, the power of Example 1 when the reflective enhancement film is laid at the gap between the cells on the photovoltaic cell is higher than that of Comparative Example 5, which indicates that the laying position of the reflective enhancement film has an impact on the power of the component, and laying the reflective enhancement film at the gap between the cells on the photovoltaic cell is better than laying it on the back glass.
[0173] Parts or structures not specifically described in the present invention may adopt existing technologies or existing products and will not be described in detail here.
[0174] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A reflective enhancement film, It is characterized in that The invention comprises a buffer layer and a substrate layer. The raw materials for preparing the buffer layer comprise ethylene polymer, mesoporous composite material, filler and additives. The raw materials for preparing the substrate layer comprise propylene polymer alloy, mesoporous composite material, filler and additives.
2. A reflective enhancement film according to claim 1, It is characterized in that The buffer layer comprises the following components by weight: Ethylene polymer 55-93 parts Mesoporous composite material 2-12 parts Filler 5-30 parts Additives 0.1-3 parts.
3. The reflective enhancement film according to claim 1, It is characterized in that The substrate layer comprises the following components by weight: Propylene polymer alloy 57-90 parts Mesoporous composite material 5-25 parts Filler 5-25 parts Additives 0.1-3 parts.
4. The reflective enhancement film according to claim 1, It is characterized in that The mesoporous composite material is composited by mesoporous material and nanomaterial, the mesoporous material is selected from at least one of MCM-41, SBA-15, and MCM-48, the nanomaterial is selected from at least one of nano zinc oxide, nano calcium carbonate, and nano barium sulfate, and the particle size of the nanomaterial is 10-200nm.
5. The reflective enhancement film according to claim 1, It is characterized in that The thickness of the buffer layer is 30-100 μm, the thickness of the substrate layer is 20-100 μm; the propylene polymer alloy is an alloy of a propylene polymer and an ethylene polymer.
6. A reflective enhancement film according to claim 1 or 5, It is characterized in that The ethylene polymer has a melting point of 70-120°C and a hardness of <80A, and is selected from one or more combinations of polyethylene, ethylene-octene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-octene copolymer, maleic anhydride grafted ethylene-butene copolymer, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene-hexene copolymer.
7. The reflective enhancement film according to claim 5, It is characterized in that The propylene polymer is selected from one or more combinations of homopolypropylene, copolymer polypropylene and block polypropylene.
8. The reflective enhancement film according to claim 1, It is characterized in that The filler is selected from one or more combinations of titanium dioxide, calcium carbonate, talc, mica, barium sulfate, silicon dioxide, and glass microspheres.
9. The reflective enhancement film according to claim 1, It is characterized in that The additives include an antioxidant and a light stabilizer. The antioxidant is a primary antioxidant or a mixture of a primary antioxidant and a secondary antioxidant. The light stabilizer is an ultraviolet absorber and / or an ultraviolet stabilizer.
10. An efficiency-enhancing photovoltaic module, It is characterized in that It comprises a reflective efficiency enhancement film as described in any one of claims 1 to 9, wherein the reflective efficiency enhancement film is laid in the gap between the photovoltaic module cells and the lower packaging film.
Citation Information
Patent Citations
Latticed high-reflection photovoltaic packaging adhesive film with double-layer composite structure and application thereof
CN109536072A
Packaging adhesive film with lattice structure as well as preparation method and application of packaging adhesive film
CN112831291A
Double-layer packaging adhesive film and photovoltaic module
CN114958240A
Wear-resistant transparent solar backboard and preparation method thereof
CN117558790A
Gap reflective film and preparation method therefor, and photovoltaic module
WO2022062303A1
